Facilitation and the invasibility of plant communities. (3rd March 2021) - Cavieres, Lohengrin A.
Abstract: One of the most studied emergent functions of plant community diversity is the resistance of diverse communities to non‐native invasions. As emphasized in this Special Feature, facilitation among native species is a key mechanism by which biodiversity increases various functions, including resistance to invasion. However, when diverse assemblages facilitate non‐native species, diversity–invasibility resistance may be compromised. Here, I review the scientific literature on plant invasion in which facilitative interactions, either among native and non‐native plant species or among non‐native species, affect community invasibility. Native species can directly facilitate non‐native species, and also generate net indirect facilitative effects through suppressing species that compete with non‐native invaders, but examples of the latter are not common. Such direct and indirect facilitation among non‐native species contributes to 'invasional meltdown' that restructures native communities. In general, facilitative interactions between native and non‐native species increased with environmental stress, suggesting that community diversity might resist invasion more effectively in environmentally favourable sites, whereas in environmentally severe sites, facilitative interactions may contribute to invasibility. Synthesis . Native and non‐native species can facilitate each other in direct and indirect ways, with important consequences for the invasibility of communities. Facilitative interactions may alter the fundamental relationship between diversity and invasibility, particularly in environmentally severe habitats. Abstract : Native and non‐native species can facilitate each other in direct and indirect ways, with important consequences for the invasibility of communities. Facilitative interactions may alter the fundamental relationship between diversity and invasibility, particularly in environmentally severe habitats.